2017
DOI: 10.3390/medicines4030047
|View full text |Cite
|
Sign up to set email alerts
|

The Chemotaxonomy of Common Sage (Salvia officinalis) Based on the Volatile Constituents

Abstract: Background: Common sage (Salvia officinalis) is a popular culinary and medicinal herb. A literature survey has revealed that sage oils can vary widely in their chemical compositions. The purpose of this study was to examine sage essential oil from different sources/origins and to define the possible chemotypes of sage oil. Methods: Three different samples of sage leaf essential oil have been obtained and analyzed by GC-MS and GC-FID. A hierarchical cluster analysis was carried out on 185 sage oil compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 57 publications
(112 reference statements)
1
38
0
Order By: Relevance
“…It is found not only in the widely known S. officinalis (e.g. Craft et al 2017;Grausgruber-Gröger et al 2012), which is discussed here in detail later on, but in many others like S. fruticosa (Karousou et al 1998), S. triloba (Longaray Delamare et al 2007), S. pilifera (Kelen and Tepe 2008), etc. However, no detectable amounts or only traces of thujones were found in other species, like S. sclareoides (Sepahvand et al 2014), S. aramiensis (Kelen and Tepe 2008), so it can not be established that thujones would be universal compounds of the genus Salvia.…”
Section: Occurence Of Thujone In Aromatic Plants Chemotaxonomic Aspectsmentioning
confidence: 83%
See 2 more Smart Citations
“…It is found not only in the widely known S. officinalis (e.g. Craft et al 2017;Grausgruber-Gröger et al 2012), which is discussed here in detail later on, but in many others like S. fruticosa (Karousou et al 1998), S. triloba (Longaray Delamare et al 2007), S. pilifera (Kelen and Tepe 2008), etc. However, no detectable amounts or only traces of thujones were found in other species, like S. sclareoides (Sepahvand et al 2014), S. aramiensis (Kelen and Tepe 2008), so it can not be established that thujones would be universal compounds of the genus Salvia.…”
Section: Occurence Of Thujone In Aromatic Plants Chemotaxonomic Aspectsmentioning
confidence: 83%
“…Jug-Dujakovic et al (2012) have examined the EO composition of 25 populations of Dalmatian sage growing in Croatia and detected three quantitative chemotypes with major compounds of athujone (15.2-33.9%) and b-thujone (3.9-37.8%). A ratio of thujone in sage oils originating from different regions (Albania, Mexico and California) varied from 17.2 to 27.4% (a-thujone) and from 3.8 to 6.0% in the case of b-thujone (Craft et al 2017). T. vulgare samples from Argentina mainly contained b-thujone (91.6%) (Gallino 1988) but Wolf et al (2012) also reported very high levels (55-79%) from wild tansy plants collected in the United States.…”
Section: Intraspecific Variability Of Thujone Content In Selected Aromentioning
confidence: 99%
See 1 more Smart Citation
“…Craft et al [23] finds that monoterpenoids α-thujone (17-27%), 1,8-cineole (12-27%) and camphor (13-21%) predominate in oil, with smaller amounts of β-thujone (3, 8-6.0%), camphene (3.5-5.3%) and sesquiterpene α-humulene (3.1-4.4%). There are reports that sage oil from Italy, Romania, the Czech Republic, Portugal and Turkey are characterized by a high content of cam-phor (22.0 to 31.79%) as a major component in the oil [43].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that α-humulene, viridiflorol and manool are predominant in young leaf oil, while the content of camphor or α-thujone is lower. In the older leaf oil, the content of α-humulene, viridiflorol and manool declines significantly with the simultaneous increase in camphor and α-thujone [23]. Cluster analysis shows that young leaf oil belongs to the α-humulene chemotype, whereas old leaf oil originating in Serbia belongs to camphor chemotype, and old leaf oil originating in Croatia belonged to the thujone chemotype [24].…”
Section: Itema 2019 Conference Proceedingsmentioning
confidence: 93%